2015
DOI: 10.1002/ajh.24007
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy results of switch from imiglucerase to velaglucerase alfa treatment in patients with type 1 Gaucher disease

Abstract: Gaucher disease (GD) is a lysosomal storage disorder; symptomatic patients with type 1 GD need long-term disease-specific therapy of which the standard of care has been enzyme replacement therapy (ERT). Thirtyeight of 40 patients (aged 9-71 years) clinically stable on ERT with imiglucerase, safely switched to a comparable dose of velaglucerase alfa (units/kg) during TKT034, a 12-month, open-label clinical study, and for 10-50 months in an extension study. The most common adverse events (AEs) judged to be drug-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The safety results from this subgroup analysis are consistent with those in the complete extension study population of 95 adult and pediatric patients [15,16]. No new safety concerns were identified in the pediatric subgroup.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The safety results from this subgroup analysis are consistent with those in the complete extension study population of 95 adult and pediatric patients [15,16]. No new safety concerns were identified in the pediatric subgroup.…”
Section: Discussionsupporting
confidence: 87%
“…In the Switch population, primary efficacy parameters were stable over time. The efficacy results in the pediatric population reflect those seen in the complete extension study population, where Overall Vela and Imi-Vela patients showed significant improvements in hematological parameters and organ volumes during the first 24 months that were maintained with longer-term treatment [16]; these efficacy parameters were generally stable in the complete Switch population [15].…”
Section: Discussionmentioning
confidence: 74%
“…Elstein et al [24] reported long-term safety findings in 38 patients from an extension study of a phase II/III trial in which patients with GD switched treatment from imiglucerase to velaglucerase alfa. Fatigue was reported as an adverse event possibly or probably related to velaglucerase alfa treatment and as an infusion-associated reaction in 2 patients [24].…”
Section: Assessment Of Fatigue In the Published Literaturementioning
confidence: 99%
“…Elstein et al [24] reported long-term safety findings in 38 patients from an extension study of a phase II/III trial in which patients with GD switched treatment from imiglucerase to velaglucerase alfa. Fatigue was reported as an adverse event possibly or probably related to velaglucerase alfa treatment and as an infusion-associated reaction in 2 patients [24]. In an observational retrospective study of 99 French patients with GD, data regarding demographics, GD history, treatment, and biological and clinical characteristics were collected; other GD-related data could also be spontaneously reported by the investigators [25].…”
Section: Assessment Of Fatigue In the Published Literaturementioning
confidence: 99%
See 1 more Smart Citation